IMPLEMENTASI NILAI-NILAI KEPEMIMPINAN DEMOKRATIS DALAM FILM “SANG KYAI” - Donny Dwi Setiabudi, Donny Dwi Setiabudi (DIGICOM : Jurnal Komunikasi dan Media, 2024)
One of the determinants of an organization's success can be determined by the way a leader directs his organization. This method can be done by choosing an appropriate leadership style to give authority or encouragement to others, such as a democratic leadership style. This study aims to provide an overview of the implementation of democratic leadership values reflected in the film "Sang Kyai", especially in the character of KH Hasyim Asy'ari as a leader. This film displays various aspects of leadership that are relevant to the concept of democratic leadership, such as integrity, responsibility, justice, and a strong vision, which are the main foundations for a leader in creating an inclusive and harmonious environment. This study was compiled using qualitative methods to collect data from relevant literature and analyze scenes in the film that depict the leadership style of KH Hasyim Asy'ari. This article also describes how democratic leadership is relevant in dealing with dynamic situations and its application in community and organizational life. The results of this study are expected to provide a deeper understanding of the relevance of democratic leadership in modern times and how these values can be applied in various management and organizational contexts today.